2012
DOI: 10.1590/s1516-14392012005000023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and catalytic properties of nanocrystaline Y2O3-coated TiO2 in the ethanol dehydration reaction

Abstract: In the present study, TiO 2 nanopowder was partially coated with Y 2 O 3 precursors generated by a sol-gel modified route. The system of nanocoated particles formed an ultra thin structure on the TiO 2 surfaces. The modified nanoparticles were characterized by high resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD) analysis, Zeta potential and surface area through N 2 fisisorption measurements. Bioethanol dehydration was used as a probe reaction to investigate the modifications on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, due to the higher percentage of Pd, it would have a higher cost compared to Pd 5, it is possible the development of alloys with Pd, Ru and Mo on carbon Vulcan as support aiming to decrease the poisoning rate and the cost of these catalysts. We encourage the performance of other tests with the catalysts of this [52][53][54][55] work to study their properties, as well as the synthesis and characterization of new proportions of the PdRuMo alloy, to obtain a greater reduction in the degree of poisoning and greater decrease in the cost of these materials. Concluding, the Table 6 presents a summary of the main characteristics and differences between the catalysts evaluated in this work, where we observed that Pd…”
Section: Perspectivesmentioning
confidence: 97%
“…However, due to the higher percentage of Pd, it would have a higher cost compared to Pd 5, it is possible the development of alloys with Pd, Ru and Mo on carbon Vulcan as support aiming to decrease the poisoning rate and the cost of these catalysts. We encourage the performance of other tests with the catalysts of this [52][53][54][55] work to study their properties, as well as the synthesis and characterization of new proportions of the PdRuMo alloy, to obtain a greater reduction in the degree of poisoning and greater decrease in the cost of these materials. Concluding, the Table 6 presents a summary of the main characteristics and differences between the catalysts evaluated in this work, where we observed that Pd…”
Section: Perspectivesmentioning
confidence: 97%
“…Most studies reported in the literature have focused on the dehydration of alcohols of two or more carbon atoms using solid acid catalysts, concluding that the main reaction product is the corresponding olefin, although in some cases it is indicated that the ether formation can become dominant at low temperatures [38][39][40]. In the case of methanol, intramolecular dehydration is not possible so the only reaction that can occur is the formation of dimethyl ether and water, although the presence of strong acid sites and high reaction temperatures can lead to obtain lighter products [41].…”
Section: Methanol Dehydration Reactionmentioning
confidence: 99%
“…ere are many reports focusing on using different methods to prepare various metal oxide supports including the sol-gel [27,28] and solvothermal methods [29,30]. In most cases, they found that different preparation methods can alter the properties of support and consequently, different catalytic properties were observed.…”
Section: Introductionmentioning
confidence: 99%